Vaccines and Vaccination against SARS-CoV-2: Considerations for the Older Population - Birgit Weinberger (Vaccines, 2021)
Age is among the most prominent risk factors for developing severe COVID-19 disease, and therefore older adults are a major target group for vaccination against SARS-CoV-2. This review focusses on age-associated aspects of COVID-19 vaccines and vaccination strategies, and summarizes data on immunogenicity, efficacy and effectiveness of the four COVID-19 vaccines, which are licensed in the US and/or Europe; namely, the two mRNA vaccines by BioNTech/Pfizer (BNT162b2) and Moderna (mRNA-1273), and the adenovector vaccines developed by AstraZeneca/University Oxford (ChAdOx1-nCoV-19, AZD1222) and Janssen/Johnson&Johnson (Ad26.COV2-S), respectively. After very high protection rates in the first months after vaccination even in the older population, effectiveness of the vaccines, particularly against asymptomatic infection and mild disease, declined at later time points and with the emergence of virus variants. Many high-income countries have recently started administration of additional doses to older adults and other high-risk groups, whereas other parts of the world are still struggling to acquire and distribute vaccines for primary vaccination. Other vaccines are available in other countries and clinical development for more vaccine candidates is ongoing, but a complete overview of COVID-19 vaccine development is beyond the scope of this article.